Injectable calcium hydroxyapatite filling repair gel and preparation method thereof

By coating hydroxyapatite calcium on dopamine-loaded MOF nanotubes and degrading in vivo, the problem of easy crystallization and hardening of hydroxyapatite calcium microspheres is solved, and the filling effect and tissue weight of long-term abundance are achieved Plastic.

CN118976146BActive Publication Date: 2025-02-11THE SIXTH MEDICAL CENT OF THE CHINESE PEOPLES LIBERATION ARMY GENERAL HOSPITAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411162919.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-02-11
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

Existing hydroxyapatite calcium injection microspheres are prone to crystallization and hardening after injection in vivo, resulting in stiffness in the injection site and difficult to remove the lumps, which may damage nerves and blood vessels, causing deformities and depressions.

Method used

Coated hydroxyapatite calcium on the outside of the dopamine-loaded MOF nanotube, and after implantation, the hydroxyapatite calcium as the shell degrades, and exists in the soft tissue in the form of calcium ions and phosphate ions to stimulate collagen. Generate and realize organizational reshaping. At the same time, the MOF nanotubes loaded with internal dopamine are cross-linked to form a composite network structure, reducing the degradation rate of the filler and achieving long-term abundance filling effect.

Benefits of technology

Through this method, hydroxyapatite calcium degraded in the body without forming lumps, achieving a long-term abundance filling effect without repeated injections, and stimulating the production of collagen, improving the repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118976146B_ABST
    Figure CN118976146B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of biogel materials, and in particular to an injectable calcium hydroxyapatite filling and repairing gel and a preparation method thereof. The present invention coats calcium hydroxyapatite on the outside of a MOF nanotube loaded with dopamine. After implantation, the calcium hydroxyapatite serving as a shell degrades and exists in the soft tissue in the form of calcium ions and phosphate ions, stimulating the production of collagen and achieving tissue remodeling. After the calcium hydroxyapatite is degraded, the MOF nanotube loaded with dopamine inside is exposed to a gel carrier and cross-linked to form a composite network structure, thereby reducing the degradation rate of the filler and achieving a long-term and full filling effect without repeated injections. The MOF nanotube encapsulated in the dopamine is evenly distributed in the soft tissue along with polymer cross-linking, and releases the contents after being degraded over time, thereby further improving the cross-linking degree of the polymer system and stimulating the production of human collagen, thereby improving the repair effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biogel materials, and in particular to an injectable calcium hydroxyapatite filling repair gel and a preparation method thereof. Background Art

[0002] Injectable filler materials have unique advantages in wrinkle removal, anti-aging, and plastic filling, and have gradually become an indispensable part of cosmetic medicine. Short-acting filler materials include hyaluronic acid, collagen, etc. Hyaluronic acid and collagen are the first generation of facial filler preparations. They degrade quickly and are difficult to maintain the clinical effect after injection. They require repeated injections, which increases safety risks. The second generation of soft tissue fillers is hyaluronic acid, and the third generation of soft tissue fillers are synthetic polymer fillers, such as polylactic acid, hydroxyapatite, and polycaprolactone.

[0003] Calcium hydroxyapatite is an inherent component of the human body with good biocompatibility, and is an efficient material for soft tissue filling. However, the solubility of calcium hydroxyapatite under physiological conditions is extremely low, especially dense calcium hydroxyapatite, which will show a lower biodegradation rate. After the existing calcium hydroxyapatite injection microspheres are injected into the body, a large number of calcium hydroxyapatite microspheres gradually crystallize and harden at the injection site to form new solid tissue, causing the injection site to become stiff and the hard mass to be difficult to remove. If the hard mass tissue is forcibly removed, it will damage the nerves and blood vessels, causing deformity and depression at the removal site.

[0004] Therefore, how to optimize and improve the structure of calcium hydroxyapatite injection microspheres and their preparation method to solve the above-mentioned defects is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide an injectable calcium hydroxyapatite filling repair gel and a preparation method thereof; the present invention coats calcium hydroxyapatite on the outside of MOF nanotubes loaded with dopamine, and after implantation, the calcium hydroxyapatite serving as a shell degrades and exists in the soft tissue in the form of calcium ions and phosphate ions, stimulating the production of collagen and achieving tissue remodeling; after the calcium hydroxyapatite is degraded, the MOF nanotubes loaded with dopamine inside are exposed to the gel carrier, cross-linked to form a composite network structure, thereby reducing the degradation rate of the filler and achieving a long-term full filling effect without the need for repeated injections; the MOF nanotubes encapsulated in the dopamine are evenly distributed in the soft tissue along with the polymer cross-linking, and release the contents after being degraded over time, thereby further improving the cross-linking degree of the polymer system and stimulating the production of human collagen, thereby improving the repair effect.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing an injectable calcium hydroxyapatite-filled repair gel comprises the following steps:

[0008] S1. Add 1-6 parts of ZrCl 4 Add 15-18 parts of DMF solution, dissolve under ultrasonic stirring for 1-2 hours, heat to 100-150°C, let stand for 1-1.5 hours, and cool to obtain solution A;

[0009] S2. Add 0.3-1 parts of TCBPE to 5-10 parts of DMF solution by mass, dissolve with ultrasonic stirring to prepare solution B;

[0010] S3. Mix the prepared solution A and solution B with 20-30 parts of hyaluronic acid, 15-20 parts of BSA solution of fibroblast growth factor, 5-10 parts of polylactic acid, and 8-10 parts of silk fibroin solution by mass, and react at 100-110° C. for 12-24 hours to fill the hyaluronic acid and BSA solution of fibroblast growth factor into the generated MOF hollow nanotubes, filter, wash, and dry to obtain MOF nanotubes with a core-shell structure;

[0011] S4. The MOF nanotubes prepared in step S3 are placed in a Tris solution containing dopamine at a pH of 8.5 and allowed to stand for 2-6 hours to obtain MOF nanotubes loaded with dopamine;

[0012] S5. The dopamine-loaded MOF nanotubes prepared in step S4 are mixed with 30-40 parts of calcium hydroxyapatite, 8-15 parts of polyethylene glycol, 20-30 parts of water, and 10-20 parts of ethanol by mass, so that the calcium hydroxyapatite adheres to the surface of the MOF nanotubes to form calcium hydroxyapatite microspheres with a core-shell structure;

[0013] S6. Mixing the core-shell calcium hydroxyapatite microspheres prepared in S5 with the gel carrier in a mass ratio of 1-5:50-80 to obtain the injectable calcium hydroxyapatite filling repair gel.

[0014] Preferably, in step S3, the mass average molecular weight of the hyaluronic acid is 20,000 to 1,000,000.

[0015] Preferably, in step S3, the concentration of the BSA solution of fibroblast growth factor is 2-8 mg / ml; the concentration of the silk fibroin solution is 1-3 mg / ml.

[0016] Preferably, in step S4, the concentration of dopamine is 0.2-0.8 mg / ml.

[0017] Preferably, in step S5, the diameter of the core-shell structured calcium hydroxyapatite microspheres is 20-45 μm.

[0018] Preferably, the preparation method of calcium hydroxyapatite is as follows:

[0019] 5-10 parts of ammonium dihydrogen phosphate and 3-4 parts of calcium nitrate tetrahydrate are mixed by mass, the pH is adjusted to 9-11, and then stirred for 1-2 hours. The obtained precipitate is collected, washed and dried to obtain the calcium hydroxyapatite.

[0020] Preferably, in step S6, the gel carrier comprises the following components by mass: 1-5 parts of gel matrix, 20-80 parts of water, 0.5-3 parts of sodium carboxymethyl cellulose, 40-50 parts of propylene glycol, and 0-1 part of lidocaine hydrochloride.

[0021] Preferably, the gel matrix is ​​a mixture of hydroxymethyl-β-cyclodextrin: isophorone diisocyanate: polyethylene glycol: 3-aminopropyltriethoxysilane: polycaprolactone in a mass ratio of 10-15: 15-30: 5-10: 1-5: 5-10.

[0022] An injectable hydroxyapatite calcium filling repair gel is prepared according to the preparation method.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention coats calcium hydroxyapatite on the outside of MOF nanotubes loaded with dopamine. After implantation, the calcium hydroxyapatite as the shell is degraded and exists in the soft tissue in the form of calcium ions and phosphate ions, stimulating the production of collagen and achieving tissue remodeling.

[0025] 2. After the calcium hydroxyapatite is degraded, the MOF nanotubes loaded with dopamine are exposed to the gel carrier and cross-linked to form a composite network structure, thereby reducing the degradation rate of the filler and achieving a long-term full filling effect without the need for repeated injections;

[0026] 3. The MOF nanotubes encapsulated inside dopamine are evenly distributed in the soft tissue along with the polymer cross-linking, and release their contents after degradation over time, thereby further increasing the cross-linking degree of the polymer system and stimulating the production of human collagen, thus improving the repair effect.

[0027] 4. The preparation process of the present invention is simple and the material acquisition is easy, which can effectively reduce the production difficulty, improve production efficiency, and reduce production costs. In addition, the filling and repair gel prepared by the present invention has good stability, excellent biocompatibility, no rejection risk, good soft tissue filling and repair effects, and has obvious economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a process flow chart for preparing the injectable calcium hydroxyapatite filling repair gel of the present invention;

[0029] Figure 2 This is a SEM image of the core-shell calcium hydroxyapatite microspheres prepared in Example 1 of the present invention;

[0030] Figure 3 This is a SEM image of the core-shell calcium hydroxyapatite microspheres prepared in Example 2 of the present invention;

[0031] Figure 4 This is a SEM image of the core-shell calcium hydroxyapatite microspheres prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] See also Figure 1-4 , the present invention provides a technical solution:

[0034] Example 1

[0035] A method for preparing an injectable calcium hydroxyapatite-filled repair gel:

[0036] S1. 3.48 g of ZrCl 4 Add into 15 ml DMF solution, dissolve under ultrasonic stirring for 1 h, heat to 100 °C and let stand for 1 h, and cool to obtain solution A;

[0037] S2. 0.51 g of TCBPE was added to 7 ml of DMF solution and dissolved by ultrasonic stirring to prepare solution B;

[0038] S3. The prepared solution A and solution B were mixed with 25 g hyaluronic acid, 15 ml of a 5 mg / ml BSA solution of fibroblast growth factor, 5 g polylactic acid, and 8 ml of a 2 mg / ml silk fibroin solution, and reacted at 100° C. for 12 h, so that the hyaluronic acid and the BSA solution of fibroblast growth factor were filled in the generated MOF hollow nanotubes, filtered, washed, and dried to obtain MOF nanotubes with a core-shell structure;

[0039] S4. The MOF nanotubes prepared in step S3 are placed in a Tris solution containing dopamine at a pH of 8.5 and allowed to stand for 2 h to obtain MOF nanotubes loaded with dopamine;

[0040] S5. The dopamine-loaded MOF nanotubes prepared in step S4 were mixed with 30 g of calcium hydroxyapatite, 8 g of polyethylene glycol, 20 g of water, and 10 g of ethanol, so that the calcium hydroxyapatite adhered to the surface of the MOF nanotubes to form calcium hydroxyapatite microspheres with a core-shell structure;

[0041] S6. 4.5 g of the core-shell calcium hydroxyapatite microspheres prepared in S5 were mixed with 50 g of the gel carrier to obtain the injectable calcium hydroxyapatite-filled repair gel;

[0042] In the above process, the mass average molecular weight of the hyaluronic acid is 500,000;

[0043] The concentration of dopamine is 0.5 mg / ml;

[0044] The preparation method of the calcium hydroxyapatite is as follows:

[0045] 50 g of ammonium dihydrogen phosphate and 30 g of calcium nitrate tetrahydrate were mixed, the pH value was adjusted to 9, and the mixture was stirred for 1 h. The resulting precipitate was collected, washed, and dried to obtain 80 g of the calcium hydroxyapatite, and 30 g of the precipitate was used in step S5 of Example 1.

[0046] The gel carrier is a mixture of 3 g of gel matrix, 50 g of water, 1 g of sodium carboxymethyl cellulose, 40 g of propylene glycol, and 0.5 g of lidocaine hydrochloride, and 50 g of the mixture is used in step S6 of Example 1;

[0047] The gel matrix is ​​a mixture of 10 g of hydroxymethyl-β-cyclodextrin, 15 g of isophorone diisocyanate, 5 g of polyethylene glycol, 3 g of 3-aminopropyltriethoxysilane, and 5 g of polycaprolactone, and 3 g of the mixture is used to prepare the gel carrier.

[0048] Example 2

[0049] A method for preparing an injectable calcium hydroxyapatite-filled repair gel:

[0050] S1. 4.51 g of ZrCl 4 Add into 15 ml DMF solution, dissolve under ultrasonic stirring for 1 h, heat to 120 °C and let stand for 1.5 h, and cool to obtain solution A;

[0051] S2. 0.74 g of TCBPE was added to 7 ml of DMF solution and dissolved by ultrasonic stirring to prepare solution B;

[0052] S3. The prepared solution A and solution B were mixed with 30 g hyaluronic acid, 18 ml of 4 mg / ml BSA solution of fibroblast growth factor, 8 g polylactic acid, and 9 ml of 3 mg / ml silk fibroin solution, and reacted at 110° C. for 18 h, so that the hyaluronic acid and fibroblast growth factor BSA solution were filled in the generated MOF hollow nanotubes, filtered, washed, and dried to obtain MOF nanotubes with a core-shell structure;

[0053] S4. The MOF nanotubes prepared in step S3 are placed in a Tris solution containing dopamine at a pH of 8.5 and allowed to stand for 4 hours to obtain MOF nanotubes loaded with dopamine;

[0054] S5. The dopamine-loaded MOF nanotubes prepared in step S4 are mixed with 35 g of calcium hydroxyapatite, 12 g of polyethylene glycol, 30 g of water, and 15 g of ethanol, so that the calcium hydroxyapatite adheres to the surface of the MOF nanotubes to form calcium hydroxyapatite microspheres with a core-shell structure;

[0055] S6. 5 g of the core-shell calcium hydroxyapatite microspheres prepared in S5 were mixed with 50 g of the gel carrier to obtain the injectable calcium hydroxyapatite-filled repair gel;

[0056] In the above process, the mass average molecular weight of the hyaluronic acid is 800,000;

[0057] The concentration of dopamine is 0.8 mg / ml;

[0058] The preparation method of the calcium hydroxyapatite is as follows:

[0059] 50 g of ammonium dihydrogen phosphate and 30 g of calcium nitrate tetrahydrate were mixed, the pH value was adjusted to 9, and the mixture was stirred for 1 h. The resulting precipitate was collected, washed, and dried to obtain 80 g of the calcium hydroxyapatite, and 35 g of the precipitate was used in step S5 of Example 2.

[0060] The gel carrier is a mixture of 4 g of gel matrix, 40 g of water, 3 g of sodium carboxymethyl cellulose, 50 g of propylene glycol, and 1 g of lidocaine hydrochloride, and 50 g of the mixture is used in step S6 of Example 2;

[0061] The gel matrix is ​​a mixture of 15 g of hydroxymethyl-β-cyclodextrin, 15 g of isophorone diisocyanate, 8 g of polyethylene glycol, 3 g of 3-aminopropyltriethoxysilane, and 6 g of polycaprolactone, and 4 g of the mixture is used to prepare the gel carrier.

[0062] Example 3

[0063] A method for preparing an injectable calcium hydroxyapatite-filled repair gel:

[0064] S1. 6g ZrCl 4 Add to 15 ml of DMF solution, dissolve under ultrasonic stirring for 1.5 h, heat to 120 °C and let stand for 1.5 h, and cool to obtain solution A;

[0065] S2. Add 1 g of TCBPE to 7 ml of DMF solution and dissolve under ultrasonic stirring to prepare solution B;

[0066] S3. The prepared solution A and solution B were mixed with 25 g hyaluronic acid, 18 ml of 8 mg / ml BSA solution of fibroblast growth factor, 6 g polylactic acid, and 8 ml of 1 mg / ml silk fibroin solution, and reacted at 110° C. for 20 h, so that the hyaluronic acid and fibroblast growth factor BSA solution were filled in the generated MOF hollow nanotubes, filtered, washed, and dried to obtain MOF nanotubes with a core-shell structure;

[0067] S4. The MOF nanotubes prepared in step S3 are placed in a Tris solution containing dopamine at a pH of 8.5 and allowed to stand for 4 hours to obtain MOF nanotubes loaded with dopamine;

[0068] S5. The dopamine-loaded MOF nanotubes prepared in step S4 are mixed with 30 g of calcium hydroxyapatite, 12 g of polyethylene glycol, 25 g of water, and 10 g of ethanol, so that the calcium hydroxyapatite adheres to the surface of the MOF nanotubes to form calcium hydroxyapatite microspheres with a core-shell structure;

[0069] S6. 7 g of the core-shell calcium hydroxyapatite microspheres prepared in S5 were mixed with 50 g of the gel carrier to obtain the injectable calcium hydroxyapatite-filled repair gel;

[0070] In the above process, the mass average molecular weight of the hyaluronic acid is 600,000;

[0071] The concentration of dopamine is 0.4 mg / ml;

[0072] The preparation method of the calcium hydroxyapatite is as follows:

[0073] 50 g of ammonium dihydrogen phosphate and 30 g of calcium nitrate tetrahydrate were mixed, the pH value was adjusted to 9, and the mixture was stirred for 1 h. The resulting precipitate was collected, washed, and dried to obtain 80 g of the calcium hydroxyapatite, and 30 g of the precipitate was used in step S5 of Example 3.

[0074] The gel carrier is a mixture of 5 g of gel matrix, 40 g of water, 3 g of sodium carboxymethyl cellulose, 50 g of propylene glycol, and 1 g of lidocaine hydrochloride, and 50 g of the mixture is used in step S6 of Example 3;

[0075] The gel matrix is ​​a mixture of 15 g of hydroxymethyl-β-cyclodextrin, 15 g of isophorone diisocyanate, 8 g of polyethylene glycol, 3 g of 3-aminopropyltriethoxysilane, and 6 g of polycaprolactone, and 5 g of the mixture is used to prepare the gel carrier.

[0076] Comparative Example

[0077] Comparative Example 1

[0078] A method for preparing an injectable calcium hydroxyapatite-filled repair gel:

[0079] S1. 25 g of hyaluronic acid, 15 ml of a 5 mg / ml BSA solution of fibroblast growth factor, 5 g of polylactic acid, and 8 ml of a 2 mg / ml silk fibroin solution were mixed and stirred for 2 h to obtain a degradable polymer sphere;

[0080] S2. The degradable polymer spheres prepared in step S1 are mixed with a Tris solution containing dopamine at a pH of 8.5, and allowed to stand for 2 hours to coat the outer surface of the degradable polymer spheres with dopamine;

[0081] S3. The degradable polymer spheres treated in step S2 are mixed with 30 g of calcium hydroxyapatite, 8 g of polyethylene glycol, 20 g of water, and 10 g of ethanol, so that the calcium hydroxyapatite adheres to the dopamine layer on the surface of the degradable polymer spheres, thereby forming calcium hydroxyapatite microspheres with a core-shell structure;

[0082] S4. 4.5 g of the core-shell calcium hydroxyapatite microspheres prepared in S3 were mixed with 50 g of the gel carrier to obtain the injectable calcium hydroxyapatite-filled repair gel;

[0083] In the above process, the mass average molecular weight of the hyaluronic acid is 500,000;

[0084] The concentration of dopamine is 0.5 mg / ml;

[0085] The preparation method of the calcium hydroxyapatite is as follows:

[0086] 50 g of ammonium dihydrogen phosphate and 30 g of calcium nitrate tetrahydrate were mixed, the pH value was adjusted to 9, and the mixture was stirred for 1 h. The resulting precipitate was collected, washed, and dried to obtain 80 g of the calcium hydroxyapatite, and 30 g of the precipitate was used in step S5 of Example 1.

[0087] The gel carrier is a mixture of 3 g of gel matrix, 50 g of water, 1 g of sodium carboxymethyl cellulose, 40 g of propylene glycol, and 0.5 g of lidocaine hydrochloride, and 50 g of the mixture is used in step S6 of Example 1;

[0088] The gel matrix is ​​a mixture of 10 g of hydroxymethyl-β-cyclodextrin, 15 g of isophorone diisocyanate, 5 g of polyethylene glycol, 3 g of 3-aminopropyltriethoxysilane, and 5 g of polycaprolactone, and 3 g of the mixture is used to prepare the gel carrier.

[0089] Comparative Example 2

[0090] A method for preparing an injectable calcium hydroxyapatite-filled repair gel:

[0091] S1. 3.48 g of ZrCl 4 Add into 15 ml DMF solution, dissolve under ultrasonic stirring for 1 h, heat to 100 °C and let stand for 1 h, and cool to obtain solution A;

[0092] S2. 0.51 g of TCBPE was added to 7 ml of DMF solution and dissolved by ultrasonic stirring to prepare solution B;

[0093] S3. The prepared solution A and solution B were mixed with 25 g hyaluronic acid, 15 ml of a 5 mg / ml BSA solution of fibroblast growth factor, 5 g polylactic acid, and 8 ml of a 2 mg / ml silk fibroin solution, and reacted at 100° C. for 12 h, so that the hyaluronic acid and the BSA solution of fibroblast growth factor were filled in the generated MOF hollow nanotubes, filtered, washed, and dried to obtain MOF nanotubes with a core-shell structure;

[0094] S4. The MOF nanotubes with core-shell structure were mixed with 30 g of calcium hydroxyapatite, 8 g of polyethylene glycol, 20 g of water, and 10 g of ethanol and stirred for 1 h, and then centrifuged, washed, dried, and the precipitate was collected;

[0095] S5. 4.5 g of the precipitate obtained in step S4 was mixed with 50 g of the gel carrier to obtain the injectable calcium hydroxyapatite-filled repair gel;

[0096] In the above process, the mass average molecular weight of the hyaluronic acid is 500,000;

[0097] The preparation method of the calcium hydroxyapatite is as follows:

[0098] 50 g of ammonium dihydrogen phosphate and 30 g of calcium nitrate tetrahydrate were mixed, the pH value was adjusted to 9, and the mixture was stirred for 1 h. The resulting precipitate was collected, washed, and dried to obtain 80 g of the calcium hydroxyapatite, and 30 g of the precipitate was used in step S5 of Example 1.

[0099] The gel carrier is a mixture of 3 g of gel matrix, 50 g of water, 1 g of sodium carboxymethyl cellulose, 40 g of propylene glycol, and 0.5 g of lidocaine hydrochloride, and 50 g of the mixture is used in step S6 of Example 1;

[0100] The gel matrix is ​​a mixture of 10 g of hydroxymethyl-β-cyclodextrin, 15 g of isophorone diisocyanate, 5 g of polyethylene glycol, 3 g of 3-aminopropyltriethoxysilane, and 5 g of polycaprolactone, and 3 g of the mixture is used to prepare the gel carrier.

[0101] Performance Testing

[0102] The core-shell calcium hydroxyapatite microspheres prepared in Example 1-3 were immersed in a newly prepared TRIS-HCL buffer solution with a mass ratio of 1:20 for degradation at a pH of 7.4. The degradation temperature was 37° C. The agglomeration of the microspheres was observed after 6 months. The results are shown below:

[0103]

[0104] The viscoelasticity, pushing resistance value, and cytotoxicity (CCK-8 method) of Examples 1-3 and Comparative Examples 1-3 were tested, and the test results are as follows:

[0105]

[0106] Referring to the above content, the cell survival rates of Examples 1-3 and Comparative Examples 1-2 are both higher than 94%, and the biocompatibility is good; the pushing resistance value of Comparative Example 2 is significantly greater than that of Examples 1-3. The presumed reason is that the MOF nanotubes are not coated with dopamine, making it difficult for calcium hydroxyapatite to adhere to the surface of the MOF nanotubes, thereby forming hydroxyapatite calcium microspheres with a core-shell structure, and the MOF nanotubes and calcium hydroxyapatite are dispersed together in the gel carrier, thereby increasing the pushing resistance value.

[0107] The examples 1-3 and comparative examples 1-2 were placed in high temperature and high pressure resistant glass bottles, sterilized in a high pressure steam sterilizer at 121°C for 30 minutes; injected into the subcutaneous tissue on both sides of the spine of the rabbit back under aseptic conditions, and the filling effect of the injection site was observed 24 hours, 1 month, 3 months, and 1 year after the injection. The results are as follows:

[0108]

[0109] Referring to the above content, it can be seen that the injectable calcium hydroxyapatite filling and repair gel provided in Examples 1-3 of the present application has no obvious rejection reaction after injection. One year after filling, the skin papule at the injection point is slightly reduced, the material is partially degraded, and there is no hardening, agglomeration or displacement. Compared with Comparative Examples 1-2, the filling effect is obvious; this strongly proves that the filling and repair gel prepared by the present invention has good stability, excellent biocompatibility, no risk of rejection, and good soft tissue filling and repair effects, which is of great significance to the development of existing soft tissue filling technology.

[0110] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an injectable calcium hydroxyapatite-filled repair gel, characterized in that: The following steps are involved: S1. Add 1-6 parts of ZrCl4 to 15-18 parts of DMF solution by mass, dissolve under ultrasonic stirring for 1-2h, heat to 100-150°C and stand for 1-1.5h, and cool to obtain solution A; S2. Add 0.3-1 parts of TCBPE to 5-10 parts of DMF solution by mass, dissolve with ultrasonic stirring to prepare solution B; S3. Mix the prepared solution A and solution B with 20-30 parts of hyaluronic acid, 15-20 parts of BSA solution of fibroblast growth factor, 5-10 parts of polylactic acid, and 8-10 parts of silk fibroin solution by mass, and react at 100-110° C. for 12-24 hours to fill the hyaluronic acid and BSA solution of fibroblast growth factor into the generated MOF hollow nanotubes, filter, wash, and dry to obtain MOF nanotubes with a core-shell structure; S4. The MOF nanotubes prepared in step S3 are placed in a Tris solution containing dopamine at a pH of 8.5 and allowed to stand for 2-6 hours to obtain MOF nanotubes loaded with dopamine; S5. The dopamine-loaded MOF nanotubes prepared in step S4 are mixed with 30-40 parts of calcium hydroxyapatite, 8-15 parts of polyethylene glycol, 20-30 parts of water, and 10-20 parts of ethanol by mass, so that the calcium hydroxyapatite adheres to the surface of the MOF nanotubes to form calcium hydroxyapatite microspheres with a core-shell structure; S6. Mixing the core-shell calcium hydroxyapatite microspheres prepared in S5 with the gel carrier in a mass ratio of 1-5:50-80 to obtain the injectable calcium hydroxyapatite filling repair gel.

2. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 1, characterized in that: In step S3, the mass average molecular weight of the hyaluronic acid is 20,000 to 1,000,000.

3. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 1, characterized in that: In step S3, the concentration of the BSA solution of fibroblast growth factor is 2-8 mg / ml; the concentration of the silk fibroin solution is 1-3 mg / ml.

4. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 1, characterized in that: In step S4, the concentration of dopamine is 0.2-0.8 mg / ml.

5. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 1, characterized in that: In step S5, the diameter of the core-shell calcium hydroxyapatite microspheres is 20-45 μm.

6. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 5, characterized in that: The preparation method of the calcium hydroxyapatite is as follows: 5-10 parts of ammonium dihydrogen phosphate and 3-4 parts of calcium nitrate tetrahydrate are mixed by mass, the pH is adjusted to 9-11, and then stirred for 1-2 hours. The obtained precipitate is collected, washed and dried to obtain the calcium hydroxyapatite.

7. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 1, characterized in that: In step S6, the gel carrier comprises the following components by mass: 1-5 parts of gel matrix, 20-80 parts of water, 0.5-3 parts of sodium carboxymethyl cellulose, 40-50 parts of propylene glycol, and 0-1 part of lidocaine hydrochloride.

8. The method for preparing an injectable calcium hydroxyapatite-filled repair gel according to claim 7, characterized in that: The gel matrix is ​​a mixture of hydroxymethyl-β-cyclodextrin: isophorone diisocyanate: polyethylene glycol: 3-aminopropyl triethoxysilane: polycaprolactone in a mass ratio of 10-15: 15-30: 5-10: 1-5: 5-10.

9. An injectable calcium hydroxyapatite filling repair gel, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Injectable hollow hydroxyapatite microsphere / chitosan composite drug carrier material and preparation method thereof

    CN103690959A

  • Composite microparticles, preparation method thereof and application of composite microparticles as carrier in administration

    CN110664778A